Dampak orientasi pasar terhadap kinerja pemasaran dan keunggulan bersaing sebagai variabel intervening pada UMKM Kota Sukabumi - Wijaya, Zeffanya Raphael; Wiyata, Mariati Tirta; Nurfalah, Rosa (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine The Impact of Market Orientation on Marketing Performance and Competitive Advantage in Sukabumi City SMEs. This study uses a quantitative method with a descriptive approach using a questionnaire distributed to 100 respondents with a sampling technique using Probability Sampling where researchers provide equal opportunities for each population to be selected as sample members who have criteria as SMEs in Sukabumi City. Testing the intrument in this study using valisity and reability tests, data analysis techniques using descriptive analysis using classical assumption test cosisting of normality test, heteroscedasticity test and multicollinearity test then regression analisys consisting of hypothesis t test and f test and using path analysis. The results of the study show that: (1) Market Orientation has an effect on Marketing Performance. (2) Market Orientation has an effect on Competitive Advantage. (3) Market Orientation has an effect on Marketing Performance with Competitive Advantage variable as an intervening variable.